2016
DOI: 10.1371/journal.pmed.1002019
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Risk of Chronic Pain: Development and Validation of a Prognostic Model (PICKUP) for Patients with Acute Low Back Pain

Abstract: BackgroundLow back pain (LBP) is a major health problem. Globally it is responsible for the most years lived with disability. The most problematic type of LBP is chronic LBP (pain lasting longer than 3 mo); it has a poor prognosis and is costly, and interventions are only moderately effective. Targeting interventions according to risk profile is a promising approach to prevent the onset of chronic LBP. Developing accurate prognostic models is the first step. No validated prognostic models are available to accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 64 publications
4
89
0
1
Order By: Relevance
“…If the authors chose to calculate AUC values, we offered further instruction on how to do so. The primary outcome of this study was pain intensity at follow-up; poor outcome was pain ≥ 3 on an 11-point NRS, which was based on Grotle et al [25] and Traeger et al [26], and follows evidence that many people with scores of < 3 consider themselves to be recovered [27]. All study authors who reported obtaining pain NRS scores were requested to dichotomise pain outcomes according to this definition.…”
Section: Methodsmentioning
confidence: 99%
“…If the authors chose to calculate AUC values, we offered further instruction on how to do so. The primary outcome of this study was pain intensity at follow-up; poor outcome was pain ≥ 3 on an 11-point NRS, which was based on Grotle et al [25] and Traeger et al [26], and follows evidence that many people with scores of < 3 consider themselves to be recovered [27]. All study authors who reported obtaining pain NRS scores were requested to dichotomise pain outcomes according to this definition.…”
Section: Methodsmentioning
confidence: 99%
“…edu.au/pain-self-checks/orebro-musculoskeletal-pain-screeningquestionnaire/) 15 and PICKUP (http:/ /pickuptool.neura.edu.au). 16 These tools are freely available online; at present, it is unclear which is best.…”
Section: Changes In Management As a Results Of The Guidelinesmentioning
confidence: 99%
“…A newer approach, endorsed in the UK National Institute for Health and Care Excellence 7 and Belgian 9 guidelines, uses simple risk prediction tools to match patients to treatment packages based on their risk of poor clinical outcome: STarT Back (http://www.keele.ac.uk/sbst/startbacktool), 14 Örebro Musculoskeletal Pain Screening Questionnaire (https://painhealth.csse.uwa.edu.au/pain-self-checks/orebro-musculoskeletal-pain-screening-questionnaire/) 15 and PICKUP (http://pickuptool.neura.edu.au). 16 These tools are freely available online; at present, it is unclear which is best.…”
Section: Treating Non‐specific Low Back Painmentioning
confidence: 99%
“…The prevalence rates for shoulder pain were higher after RND (range, 10-100%) [2][3][4][5][17][18][19][20][21] compared with MRND (range, 0-100%) [2-5, 17-19, 21] and SND (range, 9-25%) [2,5,22]. However, there is some evidence to suggest an uncertain relationship between extent of surgery and pain-related disability of the shoulder [9] that aligns with the known understanding of the multifactorial nature of pain and disability [46][47][48]. The large variation in incidence and prevalence rates likely reflects the differences in the methods, analysis and definitions used between studies rather than true differences in the rates.…”
Section: Discussionmentioning
confidence: 99%